2015
DOI: 10.1007/s00408-015-9753-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and IL-17F Promoter Single Nucleotide Polymorphism and Asthma: A Case-Control Study in South India

Abstract: We observed an association between IL-10 rs1800871 and rs1800896 SNPs and mild asthma, as well as IL-17F rs1887570 AA variant and number of allergens sensitized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…However, we found the frequency of the rs1889570 T/T genotype and T allele were markedly overrepresented in severe cases, including cases of EV71 encephalitis, when compared to mild cases and healthy controls, which suggested that the polymorphism in rs1889570 might be associated with the severity of EV71 infection in the Chinese Han population. This result is consistent with the reported results for asthma in a South Indian population [34] and tuberculosis in a Chinese population [35].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found the frequency of the rs1889570 T/T genotype and T allele were markedly overrepresented in severe cases, including cases of EV71 encephalitis, when compared to mild cases and healthy controls, which suggested that the polymorphism in rs1889570 might be associated with the severity of EV71 infection in the Chinese Han population. This result is consistent with the reported results for asthma in a South Indian population [34] and tuberculosis in a Chinese population [35].…”
Section: Introductionsupporting
confidence: 93%
“…IL-17F rs1889570 and rs4715290 located in the promotor region. Previous studies have reported the IL-17F rs1889570 gene polymorphism as being involved in several diseases, such as asthma [33,34] and tuberculosis [35]. To date, no study has been performed on the rs4715290 gene polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, 33 met the inclusion criteria (Fig. ), with 29 being candidate gene studies (Table S3) and four being GWAS .…”
Section: Methodsmentioning
confidence: 99%
“…Only four SNPs within three genes ( CRHR1: rs242941, rs1876828 ; GLCCI1: rs37973 and FCER2: rs28364072) were positively replicated at least once (Table ). Response to medication was assessed using different outcomes: lung function measurements such as changes in FEV1 over time , annual decline in FEV1 , bronchial hyperresponsiveness [BHR] to methacholine , asthma symptoms based on questionnaires and exacerbations despite treatment .…”
Section: Methodsmentioning
confidence: 99%
“…Researchers from India showed a positive correlation of the AA variant IL-17F, rs1887570, with the number of sensitizing allergens in patients with asthma [ 81 ]. Expression of IL-17C was increased in lesional AD skin [ 82 ].…”
Section: Interleukin Il-17mentioning
confidence: 99%